A comparative biochemical study of two industrially produced short‐ripened cow's milk cheeses with PDO status: Rennet‐curd Tetilla cheese and acid‐curd Cebreiro cheese. (10th February 2015) - Centeno, Juan Antonio; Rodríguez‐Alonso, Patricia; Carballo, Javier; Garabal, José Ignacio
Abstract : The aim of this study was to characterise industrial Tetilla and Cebreiro Protected Designation of Origin (PDO) Spanish cheeses from a biochemical point of view and to relate some of the biochemical parameters to the cheesemaking process. Some differences in the amounts of organic acids and free amino acids between the two types of cheese were attributed to milk characteristics and the processing technology. The most abundant volatile compounds in both types of cheese were ethanol, isopropanol and diacetyl. The simple and nonspecific volatile profiles of the cheeses appear to be related to the commercial mesophilic DL‐starters used in the manufacturing process.